Ziarah Kubur Perspektif Pendekatan Historis-Sosiologis dan Kontekstualisasinya dalam Kehidupan Kotemporer - M. Zia Al-Ayyubi; Muhammad Munif (Jurnal Studi Hadis Nusantara, 2021)
The current phenomenon of grave pilgrimage has caused reactions from various circles of society at large. There are differences of opinion (Khilafah) regarding the laws of the grave pilgrimage. The two opinions contradict each other. This is because there are different interpretations in studying one of the hadith texts as a source of istidlal law. The results of the hadith research show that the hadith about the grave pilgrimage that was endorsed by Imam Muslim in the Shohih Muslim book is of sahih quality. This is of course after going through the research steps of the hadith sanad. Then the contextualization of the hadith is related to the hadith which states that grave pilgrimage is not allowed. Therefore, in solving khilafiyah problem regarding the law of pilgrimage, if there is someone who does not agree, then do not simply punish that person with the label bid’ah. However, when differences arise, it would be nice to explore the arguments of naqli and ‘aqli so that compromises can then be made. So that in the end, Muslims are not easily divided when there is a Khilafah.